# HOMEWORK 1.

1
I) Show that the deﬁnition of probability implies:
1: Probability of the impossible event P{∅} = 0.
Note: A common technique is to partition the space, i.e. cover it completely with disjoint sets:
A family of sets A
1
, A
2
, A
3
, A
4
, etc. . . is called a partition of space S if
(1) they are mutually exclusive, A
j
∩ A
k
= ∅ for any k = j, and
(2) their union completely covers the space, S = A
1
∪ A
2
∪ A
3
∪ . . .
Note: The notation “+” introduced in class can be used in this case instead of “∪”. In other words,
the statement “the family of sets A
1
, A
2
, A
3
, A
4
, etc. . . is a partition of space S” is equivalent to
writing simply:
S = A
1
+A
1
+A
3
+ . . .
Proof. Events S and ∅ are mutually exclusive, S ∩ ∅ = ∅; they also cover the entire space,
S ∪ ∅ = S. In other words, S = S + ∅ is atrivial partition of S. Thus, using the additivity
property of probability, P(S) = P(S + ∅) = P(S) + P(∅) = 1. This is equivalent to
1 + P(∅) = 1, i.e. P(∅) = 0.
2: If
¯
A = complement of A, i.e.
¯
A∪ A = S and
¯
A∩A = ∅,
P(A) = 1 −P(
¯
A) ≤ 1.
Proof. The sets Aand
¯
Aform a partition of S. Using again the additivity property P(A) +
P(
¯
A) = P(A∪
¯
A) = P(S) = 1 which means that P(A) = 1 −P(
¯
A).
3: For any A and B,
P(A∪ B) = P(A) + P(B) −P(A∩ B).
Proof. It can be easily checked that the setsAand B∩
¯
Aare a partition of A. Then A∪B =
A∪

B ∩
¯
A

(orA∪ B = A+

B ∩
¯
A

) implies P(A∪ B) = P (A) + P

B ∩
¯
A

. Similarly
set B can be partition into sets A ∩ B and B ∩
¯
A: B = (A∩ B) +

B ∩
¯
A

meaning that
P(B) = P (A∩ B) + P

B ∩
¯
A

. Therefore
P(A∪ B) = P (A) + P

B ∩
¯
A

= P (A) + P(B) −P (A∩ B) .

4: If A ⊂ B, then
P(B) = P(A) + P(B ∩
¯
A) ≥ P(A)
1
Proof. If A ⊂ B, sets A and B ∩
¯
A are a partition of B: B = A +

B ∩
¯
A

so P(B) =
P(A) + P

B ∩
¯
A

. Since probabilities are positive numbers the inequality follows.
II) Prove that deﬁnition of the event class F implies that
1: IfA ∈ F and B ∈ F then A∩ B ∈ F .
Proof. By the deﬁnition of the event class F unions and complements of its elements be-
long to F. Since
¯
A ∪
¯
B = A∩ B, the event A ∩ B =
¯
A∪
¯
B is a combination of union and
complements, therefore t A∩ B ∈ F.
2: Both S and ∅ belong to F.
Proof. Let A ∈ F be an event (the class F is not empty). S = A ∪
¯
A and ∅ = A ∩
¯
A.They
are expressed as unions and intersections of events so they are events.
3: Finite unions and intersections of events are events.
Note: This proof is easiest done by induction. The technique is the following. Prove that the statement
is true for 2 events. Then prove that if it’s true for n events, it must be true for n + 1 events. Since
it was true for n = 2 then it has to be true for n = 2 + 1 = 3, then for n = 4, and so on, for any
value of n.
Proof. Let {A
k
}
k∈N
be a sequence of events. By deﬁnition A
1
∪ A
2
∈ F. Assume that
B =

n
k=1
A
k
∈ F. Then,

n+1
k=1
A
k
= (

n
k=1
A
k
) ∪A
n+1
= B∪A
n+1
is a union of two events,
which was shown to be an event. So

N+1
k=1
A
k
∈ F. Similar procedure for intersections of
events, and combinations of unions and intersections.
III) Show that if A∩ B = ∅, P(A) ≤ P(
¯
B).
Note: If A∩ B = ∅, it follows that A ⊂
¯
B. You can check it using Venn diagrams. Or, here’s a proof
of this based on logic:
• because A∩ B = ∅, if x is an element of A, x ∈ A, it cannot be an element of B, x / ∈ B
A∩ B = ∅ ⇔ x ∈ A & x / ∈ B
• Note that not belonging to B leaves to x only one choice, to belong to
¯
B, since S = B +
¯
B; in
other words, every element of A also belongs
¯
B, i.e.
A ⊂
¯
B.
Proof. The proof is short. Thus, A∩ B = ∅ is equivalent to A ⊂
¯
B. From the property 4 of
probability, P(A) ≤ P(
¯
B).
IV) Show that
2
1: P(A) = P(B) = P(A∩ B) ⇒P

A∩
¯
B

¯
A∩ B

= 0.
Proof. Since A =

A∩
¯
B

+(A∩ B), P(A) = P

A∩
¯
B

+P (A∩ B). But P(A) = P(A∩ B)
⇒P

A∩
¯
B

= 0. Similarly, P

B ∩
¯
A

= 0, hence the result.
2: P(A) = P(B) = 1 ⇒P (A∩ B) = 1.
Proof. Since P(A) = P(B) = 1 the probabilities
¯
A and
¯
B have to be zero (S = A +
¯
A) so
P(
¯
A) = P(
¯
B) = 0. But
P (A∩ B) = P

¯
A∪
¯
B

= 1 −P

¯
A∪
¯
B

= 1 −P(
¯
A) −P(
¯
B) + P

¯
A∩
¯
B

,
that is
P (A∩ B) = 1 + P

¯
A∩
¯
B

.
Since
¯
A∩
¯
B ⊂
¯
A, P

¯
A∩
¯
B

≤ P

¯
A

= 0, so P (A∩ B) = 1.
V) Prove that:
P(A∪ B ∪ C) = P(A) + P(B) + P(C) −P(A∩ B) −P(A∩ C) −P(B ∩ C) + P(A∩ B ∩ C).
What is the corresponding decomposition for
P(A∪ B ∪ C ∪ D) =?
Proof. Using several times the rule for the probability of the union of events yields
P(A∪ B ∪ C) = P [(A∪ B) ∪ C] = P(A∪ B) + P(C) −P [(A∪ B) ∩ C] =
= P(A) + P(B) −P(A∩ B) + P(C) −P [(A∪ B) ∩ C] .
But (A∪ B) ∩ C = (A∩ C) ∪ (B ∩ C) so
P [(A∪ B) ∩ C] = P [(A∩ C) ∪ (B ∩ C)] = P (A∩ C) + P (B ∩ C) −P [(A∩ C) ∩ (B ∩ C)]
and since (A∩ C) ∩ (B ∩ C) = A∩ B ∩ C
P(A∪ B ∪ C) = P(A) + P(B) + P(C) −P(A∩ B) −P(A∩ C) −P(B ∩ C) + P(A∩ B ∩ C).
The expression should be a sum of the probabilities of all the sets, their 2-, 3- and 4-
intersections, with alternating signs.
3